2022
DOI: 10.1016/j.resconrec.2021.105952
|View full text |Cite|
|
Sign up to set email alerts
|

From social interactions to private environmental behaviours: The case of consumer food waste

Abstract: Recent advancements in consumer studies have departed from the assumption that consumers make their decisions in isolation, based only on individual preferences and attitudes. The economics, psychology and sociology literature has been focusing on the impact of social embeddedness (i.e., of constraints due to the social context where economic activities take place) (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The empirical results of the main effects analysis and moderating effects test indicated that network embeddedness significantly moderated the relationship between reference dependence, normative internalization, and symbolic expectations with reduced RFWBs. The results of the present study are consistent with previous findings that social network interactions influence more people to adopt low-waste behaviors [72] and that knowledge sharing in social networks contributes to improved organizational performance [73]. Specifically, network embeddedness promotes the positive effect of reference dependence on reducing RFWBs.…”
Section: Moderating Effectsupporting
confidence: 92%
“…The empirical results of the main effects analysis and moderating effects test indicated that network embeddedness significantly moderated the relationship between reference dependence, normative internalization, and symbolic expectations with reduced RFWBs. The results of the present study are consistent with previous findings that social network interactions influence more people to adopt low-waste behaviors [72] and that knowledge sharing in social networks contributes to improved organizational performance [73]. Specifically, network embeddedness promotes the positive effect of reference dependence on reducing RFWBs.…”
Section: Moderating Effectsupporting
confidence: 92%
“…This finding is in line with previous literature observations that food waste is the final outcome of a long chain of actions, from food purchase to leftover management, which leaves a limited role to intentionality and causes the emerging of an "intention-action gap" (Evans, 2011;Richetin et al, 2012;Watson and Meah, 2012;Hebrok and Heidenstrøm, 2019;Giordano et al, 2018Giordano et al, , 2019Piras et al, 2022a). It is also in line with Sorokowska et al (2020), whereby children perceive food waste as something bad but do not act accordingly.…”
Section: Food Waste Behaviour In School Canteens: Values Education An...supporting
confidence: 91%
“…Both approaches have been questioned due to their overreliance on intention-behaviour coherence, which ignores the context where behaviours happen (Stöckli et al, 2018;Soma et al, 2020). Some studies have analysed the so-called "attitude-behaviour gap" (Kollmuss and Agyeman, 2002;Graham-Rowe et al, 2015;Piras et al, 2022a), or the "behaviour-outcome gap" (Setti et al, 2018), whereby subjects declaring not to waste or to feel disgusted by wasting food, actually waste quantities similar to others without realising it (Schanes et al, 2018;Giordano et al, 2018Giordano et al, , 2019Elimelech et al, 2019), or feel absolved for their own food waste production due to lack of time or for other practical reasons (Van Geffen et al, 2020). Likewise, many scholars have demonstrated that food-wasting habits may not always correspond to awareness of the issue (Evans, 2011;Richetin et al, 2012;Watson and Meah, 2012;Ganglbauer et al, 2013;Spurling et al, 2013; Hebrok and Heidenstrøm, ioural traits", "values and attitudes" to indicate the order that a consumer (here, student) gives to specific characteristics of a good/service, resulting in a decision.…”
Section: Values Attitudes and Food Wastementioning
confidence: 99%
“…Campaigns stressing the negative consequences of food waste are expected to encourage food waste prevention behaviors. Dissonance‐based campaigns aimed at making consumers aware of the gap between their beliefs and their current behavior deserve special consideration (Pelt et al, 2020; Piras et al, 2022). Such campaigns have been reported to be effective across different behavioral domains, including environmental behaviors (Freijy & Kothe, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Higher awareness of the negative consequences of food waste is expected to activate moral norms, which could further contribute to encourage prevention behaviors. Piras et al (2022) have recently shown recommended communication campaigns depicting food waste prevention as the social norm. However, it should be stressed that these messages may not work for all consumers.…”
Section: Implications For the Development Of Strategies To Reduce Hou...mentioning
confidence: 99%